2014
DOI: 10.1051/0004-6361/201423756
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale chromospheric jets above a sunspot light bridge

Abstract: Context. The chromosphere above sunspot umbrae and penumbrae shows several different types of fast dynamic events such as running penumbral waves, umbral flashes, and penumbral microjets. Aims. The aim of this paper is to identify the physical driver responsible for the dynamic and small-scale chromospheric jets above a sunspot light bridge.Methods. High-resolution broadband filtergrams of active region NOAA 11271 in Ca ii H and G band were obtained with the Solar Optical Telescope on board Hinode. We identifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 45 publications
11
77
0
Order By: Relevance
“…The bright front may be caused by heating to TR temperatures through either a shock front or compression when the chromospheric surges hit the overlying atmosphere. It is worth mentioning that previously magnetic reconnection was usually suggested to trigger these surges (Asai et al 2001;Shimizu et al 2009;Louis et al 2014;Toriumi et al 2015). IRIS observations have also revealed occasionally occurring reconnection events at light bridges (e.g., Song et al 2017;Hou et al 2017).…”
Section: Dynamics In the Tr Above Sunspotsmentioning
confidence: 86%
See 1 more Smart Citation
“…The bright front may be caused by heating to TR temperatures through either a shock front or compression when the chromospheric surges hit the overlying atmosphere. It is worth mentioning that previously magnetic reconnection was usually suggested to trigger these surges (Asai et al 2001;Shimizu et al 2009;Louis et al 2014;Toriumi et al 2015). IRIS observations have also revealed occasionally occurring reconnection events at light bridges (e.g., Song et al 2017;Hou et al 2017).…”
Section: Dynamics In the Tr Above Sunspotsmentioning
confidence: 86%
“…Another type of oscillatory phenomenon in sunspots is the surge-like up-and-down motion above some light bridges (Asai et al 2001;Shimizu et al 2009;Louis et al 2014;Toriumi et al 2015). These surges are usually observed in chromospheric images.…”
Section: Dynamics In the Tr Above Sunspotsmentioning
confidence: 99%
“…1). Some of these structures behaved as bright streaks and flashes, as well as resembling the chromospheric calcium jets (Louis et al 2014a; see the yellow arrow in Fig. 1d).…”
Section: Formation and Evolution Of Afssmentioning
confidence: 90%
“…LBs were also found to be associated with many aspects of solar activity, such as surges (Asai et al 2001), filaments (Rimmele 2008), small-scale chromospheric jets (Louis et al 2014a), and coronal jets (Liu 2012). By analyzing the magnetic fields of a LB, Shimizu et al (2009) found that highly twisted flux tubes with current were trapped by the LB canopy structure and were responsible for the chromospheric ejections.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation